Systematic identification of NF90 target RNAs by iCLIP analysis - Lodde, Valeria; Floris, Matteo; Munk, Rachel; Martindale, Jennifer L.; Piredda, Davide; Napodano, Catello Mario Panu; Cucca, Francesco; Uzzau, Sergio; Abdelmohsen, Kotb; Gorospe, Myriam; Noh, Ji Heon; Idda, M. Laura (Scientific reports, 2022)
RNA-binding proteins (RBPs) interact with and determine the fate of many cellular RNAs directing numerous essential roles in cellular physiology. Nuclear Factor 90 (NF90) is an RBP encoded by the interleukin enhancer-binding factor 3 ( ILF3 ) gene that has been found to influence RNA metabolism at several levels, including pre-RNA splicing, mRNA turnover, and translation. To systematically identify the RNAs that interact with NF90, we carried out iCLIP (individual-nucleotide resolution UV crosslinking and immunoprecipitation) analysis in the human embryonic fibroblast cell line HEK-293. Interestingly, many of the identified RNAs encoded proteins involved in the response to viral infection and RNA metabolism. We validated a subset of targets and investigated the impact of NF90 on their expression levels. Two of the top targets, IRF3 and IRF9 mRNAs, encode the proteins IRF3 and IRF9, crucial regulators of the interferon pathway involved in the SARS-CoV-2 immune response. Our results support a role for NF90 in modulating key genes implicated in the immune response and offer insight into the immunological response to the SARS-CoV-2 infection.